Why ask? On the library’s user satisfaction surveys conducted within the framework of the Performance Analysis for Polish Research Libraries project - Edyta Strzelczyk; Lidia Derfert-Wolf (Forum Bibliotek Medycznych, 2019)
After over ten years of the implementation of the Performance Analysis for Polish Research Libraries project (Polish: AFBN, conducted since 2001), a new field marked "User satisfaction" was included in the form containing statistical data and performance indicators for 2017. What does this name mean? What value should be entered here? How to determine and interpret it? These are just some of the questions arising when seeing the "User satisfaction" indicator for the first time. This indicator should be determined by means of direct measurements (questionnaire surveys) held among library users using the methodology prepared for the needs of the project. The key elements influencing the correctness of the performance of user satisfaction surveys will be discussed: the structure of the research tool, the logic of sampling, the processing and analysis of the collected data. The nationwide university library user satisfaction surveys carried out in the first quarter of 2017 along with a brief discussion of the AFBN project will serve as a background for presenting specific examples and solutions. The answer to the question formulated in the subject of the presentation: Why ask? - will allow determining the role of a satisfied user and the consequences of dissatisfied library service users for the functioning of the libraries